Structure-function relationship of a bio-pesticidal trypsin/chymotrypsin inhibitor from winged bean - Banerjee, Sayanika; Giri, Ashok P.; Gupta, Vidya S.; Dutta, Samir Kumar (International Journal of Biological Macromolecules, 2017)
Protease inhibitors are essential bio-molecules that serve as a model system for the study of protein structure and protease-protease inhibitor interaction. We here report a bi-functional serine protease inhibitor from winged bean (WBCTI) that completely retains its inhibitory property against trypsin and chymotrypsin even after heating at 70 degrees C. Detailed circular dichroism and fluorescence studies at different temperatures, 30-90 degrees C, have been performed to understand the reason behind thermal stability of the protein. On the basis of our results it appears that WBCTI maintains its canonical structure up to 70 degrees C. Above that the heat induced conformational change becomes irreversible which causes aggregation followed by precipitation of the protein. Moreover, the activity and stability of the secondary structure are found to decrease drastically in presence of dithiothreitol indicating that the protein acquires additional stability for the occurrence of two disulfide bonds. In addition to the structural characterization, an important property of WBCTI against the polyphagous pest Helicoverpa armigera has been explored in present study. WBCTI has showed reasonable inhibition of the mid-gut proteases of H. armigera. In artificial feeding trial through addition of WBCTI in diet resulted in significant growth retardation, delayed pupae formation and higher mortality of H. armigera larvae. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Disulfide reduction; Heat stable; Pesticidal; Trypsin/Chymotrypsin inhibitor; Winged bean